Vitamin B12 Status in Long-Term Metformin Treated Type 2 Diabetes Mellitus Patients (Bangladesh Journal of Medicine, 2022)
Background: The association between long-term use of metformin and low vitamin B12 levels in patients with type 2 diabetes mellitus (T2DM) has been proven. However, the prevalence among metformin induced vitamin B12 deficiency in T2DM patients showed considerable variations among the studies. The potential of deficiency to cause new onset or worse preexisting peripheral neuropathy in T2DM patients has been investigated with conflicting results.The objective of this study is to determine the frequency of vitamin B12 deficiency among patients with T2DM patients on metformin therapy compared to those who are not taking metformin.Methods: This crosssectional analytical study was conducted at the Department of Medicine, in Sylhet M. A. G. Osmani Medical College &Hospital, Sylhet. Total 100 patients’ withT2DM were selected according to inclusion and exclusion criteria following informed written consent. They were divided into two groups; each groups contains 50 patients. Group-I included patients who were taking metformin for e”1 year and Group-II included patients who were not taking metformin for at least 1 year. Detailed history taking, proper clinical examinations and relevant investigations were done. After collection of all the required data, final analysis was carried out by using the SPSS version 22.0.Results: Among 100 patients of T2DM, mean age were 55.4±15.62 and 55.24±16.76 years, respectively among Group- I and Group-II. They were similar in terms of demographic profile. About 16.0% patients of group- I had vitamin B 12 deficiency and 6.0% had vitamin B 12 deficiency in Group-II. The mean serum Vitamin B 12 was 481.52±283.37 (pgm/mL) in group-I and 600.85±294.2 (pgm/mL) in group-II. The difference of serum Vitamin B 12 was statistically significant (p